The Effect of SPEOS Method and Acupuncture Point Gb 21 To Increase Breast Milk Production - Nia Clarasari MP; Jenny Kartika; Rita Kamalia; sari wahyuni (MBUnivPress, 2022)
The success of breastfeeding in the early puerperium can affect the success of exclusive breastfeeding. This is because the production of breast milk for infants is sufficient for growth. One method to increase breast milk production is the SPEOS method (Endorphin, Oxytocin, and Suggestive Stimulation) and the Acupuncture method at GB 21 point. This study aims to determine the effect of the SPEOS method and GB 21 acupuncture method on increasing breast milk production at the Az – Maternity Clinic. Zahwa South Sumatra in 2020. Where breast milk production is assessed from the amount of milk that comes out and can be accepted by the baby, measured by using the baby's weight indicator. Measurements were made on day 5 and day 10. This study uses a quasi-experimental design with a non-equivalent approach Pretest-Posttest with Control Group. The subjects in this study were normal postpartum mothers who gave birth at the Az – Zahwa clinic. The total sample size was 90 people with 30 samples being divided into the SPEOS method group, 30 samples in the GB 21 acupuncture method and 30 in the control group. This research was conducted in October-November 2020. The data were analyzed using the T dependent test and the one way ANOVA test. The results of the study obtained the average difference in body weight before and after the study. In the control group, the average difference was -5.0 (86.4) grams, in the SPEOS group the average difference in body weight was 22.1 (57.3) grams, in the GB 21 Acupuncture group the average difference in body weight is -41.3 (298.7) grams. The results of statistical tests showed that there was no significant difference in body weight after the study in the three groups (p value 0.405). This shows that there is no difference in the three methods of milk production.